Hire-Me-Not? The Influence of Grades and University Type on Labor Market Success - Kristinsson, Kari; Guðjonsson, Sigurður; Minelgaite, Inga; Christiansen, Tinna Dahl (Pedagogika, 2023)
How effective is education as a signal for attracting future employers? With a sample of 143 human resource managers from Iceland's 300 largest companies, we conducted a framed field experiment to see if academic achievement and school choice influenced the job candidate's employability and salary. Candidates from public and private schools were seen as equally qualified and hirable, with public school candidates potentially getting offered a 9.8% higher salary.